"Highly Exposed Chinese Herbal Medicine" Combined With Apatinib as Maintenance Treatment Following First-Line or Second-Line Chemotherapy for Extensive-Stage Small-Cell Lung Cancer: A Single-Arm, Prospective Study. Issue 4 (26th October 2021) - Wang, Mingqi; Jiang, Haili; Zhang, Mei; Chen, Yang; Wang, Ting; Li, Ping
This study aimed to evaluate the efficacy and safety of "highly exposed Chinese herbal medicine" combined with apatinib as maintenance treatment following first-line or second-line chemotherapy in patients with ES-SCLC. A total of 23 patients with ES-SCLC were included in this single-arm prospective study (ChiCTR2100045255). "Highly exposed Chinese herbal medicine" combined with apatinib was administered each day after the chemotherapy for maintenance treatment. The primary endpoint of the study was median PFS, while the secondary endpoints included median OS, DCR, ORR, AE, and the association of "highly exposed Chinese herbal medicine" with PFS and OS. Three and 16 patients achieved partial response (PR) and stable disease (SD), respectively, and four patients were with disease progression (PD). The ORR of the patients was 13.0%, DCR was 83.0%, median PFS was 5.0 months, and median OS was 18.0 months. The major AE included secondary hypertension and hand-foot syndrome. Oral intake of Chinese herbal medicine for ≥ 6 months was associated with longer PFS. Hand-foot syndrome was an independent predictive factor for PFS. The statistical analysis suggested no independent influencing factors for OS. "Highly exposed Chinese herbal medicine" combined with apatinib is effective and relatively safe as the maintenance treatment for ES-SCLC patients who undergo first-line or second-line chemotherapy.